Preparation method of SnO2-coated TiO2 double-shell packaged amorphous GeO2 ternary anode material

Through the preparation method of SnO2@TiO2 bi-shell encapsulated amorphous GeO2 ternary anode material, the problem of volume changes and poor conductivity of metal oxide anode materials is solved, and the electrochemical performance of lithium-ion batteries is significantly improved.

CN119742356AActive Publication Date: 2025-04-01KUNMING UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510020313.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-01
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The metal oxide anode material changes greatly during the circulation process and has poor conductivity, resulting in poor electrochemical performance.

Method used

The SnO2@TiO2 bi-shell encapsulated amorphous GeO2 ternary anode material was prepared by hydrothermal method, and the GeO2@C microsphere template and tin tetrachloride were reacted with room temperature stirring reaction to form GeO2@C@SnO2 composite powder, and then the GeO2@C@SnO2 precursor powder was prepared by sol-gel method, and the final anode material was calcined in an air atmosphere.

Benefits of technology

It effectively alleviates the volume changes of GeO2 materials during charging and discharging, improves the conductivity and cycling performance of the materials, and improves the comprehensive electrochemical performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a preparation method of an amorphous GeO2 ternary anode material packaged by a SnO2-coated TiO2 double-shell layer, and belongs to the technical field of composite electrode materials. According to the invention, commercial GeO2, stannic chloride and tetrabutyl titanate are adopted as raw materials; the preparation method comprises the following steps: preparing a GeO2 (at) C microsphere template by adopting a hydrothermal method, adding tin tetrachloride into dispersion liquid of the GeO2 (at) C microsphere template, carrying out stirring reaction at room temperature, and carrying out solid-liquid separation and drying to prepare GeO2 (at) C (at) SnO2 composite powder; the preparation method comprises the following steps: preparing GeO2 (at) C (at) SnO2 (at) TiO2 precursor powder from titanium source tetrabutyl titanate and GeO2 (at) C (at) SnO2 composite powder through a sol-gel method, and calcining the GeO2 (at) C (at) SnO2 (at) TiO2 precursor powder in an air atmosphere to obtain the SnO2 (at) TiO2 double-shell packaged amorphous GeO2 ternary anode material. The structure of the anode material can effectively solve the problem of volume expansion of a metal oxide anode material, a rapid Li < + > transmission path is constructed, and the comprehensive electrochemical performance of the lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material, belonging to the technical field of composite electrode materials. Background Art

[0002] Lithium-ion batteries have excellent portability, environmental friendliness, strong independence, light weight, high capacity, long cycle life, and are widely used in the field of electric and plug-in hybrid vehicles. There is an urgent need to develop higher-performance lithium-ion batteries. Lithium-ion batteries are composed of positive and negative electrodes, electrolytes, and separators, among which the negative electrode material plays a vital role in the overall performance of the battery.

[0003] Metal oxides (such as SiO2, Fe3O4, SnO2, GeO2 and TiO2) are very promising negative electrode materials with advantages such as high specific capacity, high safety, easy modification and composite, so they can replace traditional graphite negative electrodes. However, they undergo large volume changes during the cycle, resulting in electrode crushing, and the conductivity of the oxides is inherently low, which leads to poor electrode stability and rate performance. Although studies have shown that their performance can be stabilized, for example, ultra-small size design: nanomaterials shorten the diffusion path of lithium ions and accelerate charge transfer during the insertion / deinsertion process; protective layer structure: nanotubes, nanopores, hollow spheres, yolk-shell structures, etc., further improvements are still needed for practical application. Summary of the invention

[0004] In view of the problem that the metal oxide-based anode material in the technical solution undergoes a large volume change during the cycle and the poor electrochemical performance caused by the poor conductivity of the oxide, the present invention proposes a method for preparing a SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material, wherein a GeO2@C microsphere template is prepared by a hydrothermal method, tin tetrachloride is added to the dispersion of the GeO2@C microsphere template, and after stirring at room temperature, the solid-liquid separation and drying are performed to obtain a GeO2@C@SnO2 composite powder; a GeO2@C@SnO2@TiO2 precursor powder is prepared by a sol-gel method using titanium source tetrabutyl titanate and GeO2@C@SnO2 composite powder, and the GeO2@C@SnO2@TiO2 precursor powder is calcined in an air atmosphere to obtain a SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material. The structure of the anode material of the present invention can effectively solve the volume expansion problem of the metal oxide anode material and construct a fast Li + transmission path to improve the comprehensive electrochemical performance of lithium-ion batteries.

[0005] A method for preparing a SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material, the specific steps are as follows: (1) Ammonia water was added dropwise to the aqueous solution containing GeO2. After GeO2 was completely dissolved, glucose was added and stirred at room temperature for 1-3 h to obtain solution A. Solution A was added to a high temperature and high pressure reactor and kept at 150-200 °C for 6-24 h. The solid and liquid were separated and the solid was dried to obtain product B (microsphere template of GeO2@C). (2) Product B was uniformly dispersed in a deionized water-ethanol mixed solution to obtain a product B dispersion, tin tetrachloride was added to the product B dispersion and mixed uniformly to obtain a solution C, solution C was stirred at room temperature for 2-4 hours, ethanol was centrifuged to wash the precipitate, and dried to obtain product D (GeO2@C@SnO2 composite powder); (3) Dispersing product D uniformly in an ammonia-ethanol mixed solution to obtain a product D dispersion, adding tetrabutyl titanate, stirring and reacting at room temperature for 1-3 hours, washing the precipitate by centrifugation with ethanol, and drying to obtain a precursor product E (GeO2@C@SnO2@TiO2 precursor powder); (4) The precursor product E is calcined at a temperature of 400-600°C for 2-8 hours, and then cooled to room temperature in the furnace to obtain a SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material with a hollow core-shell structure.

[0006] Preferably, in the solution A of step (1), the mass concentration of GeO2 is 1-5%, the mass concentration of ammonia water is 1-5%, and the mass concentration of glucose is 5-15%.

[0007] Preferably, the volume ratio of ethanol to deionized water in the deionized water-ethanol mixed solution in step (2) is 3:1-5, the mass concentration of product B in solution C is 1-6%, and the mass concentration of tin tetrachloride is 1-6%.

[0008] Preferably, in the ammonia-ethanol mixed solution of step (3), the mass concentration of ammonia water is 1-5%, the mass concentration of product D in solution E is 2-7%, and the mass concentration of tetrabutyl titanate is 0.5-3%.

[0009] Preferably, the calcination temperature in step (4) is 400-600° C. and the calcination time is 2-8 hours.

[0010] The beneficial effects of the present invention are: (1) The SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material of the present invention includes, from the inside to the outside, a core amorphous GeO2, an inner shell SnO2, and a TiO2 outer shell encapsulating amorphous GeO2, and the hollow portion between the core and the shell can achieve a larger specific surface area, which promotes the full reaction between the electrolyte and the active material, and alleviates the volume change of the GeO2 material during the charge and discharge process, thereby improving the cycle performance of the GeO2 anode; (2) The inner SnO2 shell of the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material of the present invention is a P-type semiconductor, and the GeO2 core is an N-type semiconductor. The two form a PN heterojunction to construct a built-in electric field, which can significantly improve the conductivity of the material; (3) The solid TiO2 shell of the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material of the present invention can prevent the hollow structure from collapsing, so that the electrode forms a stable solid electrolyte interface film during the cycle; (4) The SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material of the present invention takes into account the respective advantages of GeO2, SnO2 and TiO2, has a simple preparation process and excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 This is a scanning electron microscope image of the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material in Example 1; Figure 2 The charge and discharge curves of the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material in Example 1; Figure 3 The cycle performance spectrum of the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material in Example 1; Figure 4 The X-ray diffraction pattern of the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material in Example 2; Figure 5 The scanning electron microscope and EDS spectrum of the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material in Example 2; Figure 6 The charge and discharge curves of the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material in Example 2; Figure 7 The cycle performance spectrum of the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material in Example 2; Figure 8 This is a scanning electron microscope image of the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material in Example 3; Fig. 9 The charge and discharge curves of the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material in Example 3; Fig.10 This is the cycling performance spectrum of the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material in Example 3. DETAILED DESCRIPTION

[0012] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.

[0013] Example 1: A method for preparing a SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material, the specific steps are as follows: (1) Ammonia water was added dropwise to an aqueous solution containing commercial GeO2. After GeO2 was completely dissolved, glucose was added and stirred at room temperature for 1 hour to obtain solution A. Solution A was added to a high temperature and high pressure reactor and kept at 150°C for 24 hours. The solid and liquid were separated and the solid was dried to obtain product B (GeO2@C microsphere template). The mass concentration of GeO2 in solution A was 1%, the mass concentration of ammonia water was 1%, and the mass concentration of glucose was 5%. (2) Dispersing product B uniformly in a deionized water-ethanol mixed solution to obtain a product B dispersion, adding tin tetrachloride to the product B dispersion and mixing uniformly to obtain solution C, stirring solution C for reaction at room temperature for 2 h, washing the precipitate by centrifugation with ethanol, and drying to obtain product D (GeO2@C@SnO2 composite powder); the volume ratio of ethanol to deionized water in the deionized water-ethanol mixed solution is 3:5, the mass concentration of product B in solution C is 1%, and the mass concentration of tin tetrachloride is 1%; (3) Under stirring conditions, the product D is uniformly dispersed in an ammonia-ethanol mixed solution to obtain a product D dispersion, tetrabutyl titanate is added, and the reaction is stirred at room temperature for 1 hour. The precipitate is washed by centrifugation with ethanol, and dried to obtain a precursor product E (GeO2@C@SnO2@TiO2 precursor powder); the mass concentration of ammonia in the ammonia-ethanol mixed solution is 1%, the mass concentration of product D in solution E is 2%, and the mass concentration of tetrabutyl titanate is 0.5%; (4) The precursor product E was calcined in an air atmosphere at 400°C for 8 h, and then cooled to room temperature to obtain a SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material with a hollow core-shell structure; The scanning electron microscope morphology of the SnO2@TiO2 double shell encapsulated amorphous GeO2 ternary anode material in this embodiment is shown in Figure 1 ,from Figure 1 It can be seen that the prepared anode material has a hollow core-shell structure, with a core diameter of about 1.5µm, a microsphere diameter of about 5µm, and nanoparticles attached to the shell; In this embodiment, the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material is used as the anode of the lithium-ion half-cell. The active material: acetylene black: PVDF = 7:2:1 is ground and evenly coated on the copper foil. After vacuum drying, it is used as the battery anode. The metal lithium sheet is used as the counter electrode. The electrolyte is 1 mol / L LiPF6, and the volume fraction of FEC solution is added. The charge and discharge curves of the first three cycles of the lithium-ion half-cell are shown in FIG. Figure 2 , 130 cycles performance see Figure 3 ,Depend on Figure 2 and 3 It can be seen that the charge / discharge specific capacities of the first, second and third times are 629 / 800, 597 / 689 and 576 / 640 mAh g −1 , and their coulombic efficiencies were 78.6%, 86.7% and 90.0% respectively. The coulombic efficiency increased with the increase of the number of cycles. At a current density of 0.2C, after 130 cycles, it still maintained 400.15mAh g −1 The reversible capacity of indicates that the anode material of this embodiment has excellent reversibility and cycle stability.

[0014] Example 2: A method for preparing a SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material, the specific steps are as follows: (1) Ammonia water was added dropwise to an aqueous solution containing commercial GeO2, and glucose was added after GeO2 was completely dissolved. The mixture was stirred at room temperature for 2 h to obtain solution A, which was added to a high-temperature and high-pressure reactor. The reaction was carried out at 180°C for 14 h, and the solid-liquid separation was performed. The solid was dried to obtain product B (GeO2@C microsphere template); the mass concentration of GeO2 in solution A was 3%, the mass concentration of ammonia water was 3%, and the mass concentration of glucose was 10%; (2) Dispersing product B uniformly in a deionized water-ethanol mixed solution to obtain a product B dispersion, adding tin tetrachloride to the product B dispersion and mixing uniformly to obtain solution C, stirring solution C for reaction at room temperature for 3 hours, washing the precipitate by centrifugation with ethanol, and drying to obtain product D (GeO2@C@SnO2 composite powder); the volume ratio of ethanol to deionized water in the deionized water-ethanol mixed solution is 3:3, the mass concentration of product B in solution C is 4%, and the mass concentration of tin tetrachloride is 4%; (3) Under stirring conditions, the product D is uniformly dispersed in an ammonia-ethanol mixed solution to obtain a product D dispersion, tetrabutyl titanate is added, and the reaction is stirred at room temperature for 2 hours. The precipitate is washed by centrifugation with ethanol, and dried to obtain a precursor product E (GeO2@C@SnO2@TiO2 precursor powder); the mass concentration of ammonia in the ammonia-ethanol mixed solution is 3%, the mass concentration of product D in solution E is 5%, and the mass concentration of tetrabutyl titanate is 1.5%; (4) The precursor product E was calcined in an air atmosphere at a temperature of 500°C for 6 h, and then cooled to room temperature in the furnace to obtain a SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material with a hollow core-shell structure; The X-ray diffraction spectrum of the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material in this embodiment is shown in Figure 4 ,from Figure 4 It can be seen that the anode material corresponds to the standard diffraction card of TiO2 at 2θ=25.3°, 37.9°, and 48.1°, and corresponds to the standard diffraction card of SnO2 at 2θ=33.8° and 51.8°. A bun peak appears at 2θ=26.4°, indicating that GeO2 has an amorphous structure. The morphology and element distribution of the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material in this embodiment are shown in Figure 5 ,from Figure 5 It can be seen that the anode material is composed of four elements: O, Ge, Sn, and Ti. The Sn and Ti elements are evenly distributed on the inner and outer shells of the hollow microspheres. The core is amorphous GeO2, while the SnO2 inner shell and the TiO2 outer shell cover the amorphous GeO2. In this embodiment, the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material is used as the anode of the lithium-ion half-cell. The active material: acetylene black: PVDF = 7:2:1 is ground and evenly coated on the copper foil. After vacuum drying, it is used as the battery anode. The metal lithium sheet is used as the counter electrode. The electrolyte is 1 mol / L LiPF6, and the volume fraction of FEC solution is added. The charge and discharge curves of the first three cycles of the lithium-ion half-cell are shown in FIG. Figure 6 , 130 cycles performance see Figure 7 ,Depend on Figure 6 and 7 It can be seen that the charge / discharge specific capacities of the first, second and third times are 746 / 952, 702 / 815 and 677 / 756 mAh g −1 , and their coulombic efficiencies were 78.4%, 86.1%, and 89.6%, respectively. The coulombic efficiency increased with the number of cycles. At a current density of 0.2C, after 130 cycles, it still maintained 429mAh g −1 The reversible capacity of indicates that the anode material of this embodiment has excellent reversibility and cycle stability.

[0015] Example 3: A method for preparing a SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material, the specific steps are as follows: (1) Ammonia water was added dropwise to an aqueous solution containing commercial GeO2. After GeO2 was completely dissolved, glucose was added and stirred at room temperature for 3 h to obtain solution A. Solution A was added to a high temperature and high pressure reactor and kept reacting at 200°C for 7 h. The solid and liquid were separated and the solid was dried to obtain product B (GeO2@C microsphere template). The mass concentration of GeO2 in solution A was 5%, the mass concentration of ammonia water was 5%, and the mass concentration of glucose was 15%. (2) Dispersing product B uniformly in a deionized water-ethanol mixed solution to obtain a product B dispersion, adding tin tetrachloride to the product B dispersion and mixing uniformly to obtain solution C, stirring solution C for reaction at room temperature for 4 hours, washing the precipitate by centrifugation with ethanol, and drying to obtain product D (GeO2@C@SnO2 composite powder); the volume ratio of ethanol to deionized water in the deionized water-ethanol mixed solution is 2:1, the mass concentration of product B in solution C is 6%, and the mass concentration of tin tetrachloride is 6%; (3) Under stirring conditions, the product D is uniformly dispersed in an ammonia-ethanol mixed solution to obtain a product D dispersion, tetrabutyl titanate is added, and the reaction is stirred at room temperature for 3 hours. The precipitate is washed by centrifugation with ethanol, and dried to obtain a precursor product E (GeO2@C@SnO2@TiO2 precursor powder); the mass concentration of ammonia in the ammonia-ethanol mixed solution is 5%, the mass concentration of product D in solution E is 7%, and the mass concentration of tetrabutyl titanate is 3%; (4) The precursor product E was calcined in an air atmosphere at 600°C for 2 h, and then cooled to room temperature to obtain a SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material with a hollow core-shell structure; The scanning electron microscope morphology of the SnO2@TiO2 double shell encapsulated amorphous GeO2 ternary anode material in this embodiment is shown in Figure 8 ,from Figure 8 It can be seen that the prepared anode material has a hollow core-shell structure, with a core diameter of about 2µm, a microsphere diameter of about 6µm, and nanoparticles attached to the shell; In this embodiment, the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material is used as the anode of the lithium-ion half-cell. The active material: acetylene black: PVDF = 7:2:1 is ground and evenly coated on the copper foil. After vacuum drying, it is used as the battery anode. The metal lithium sheet is used as the counter electrode. The electrolyte is 1 mol / L LiPF6, and the volume fraction of FEC solution is added. The charge and discharge curves of the first three cycles of the lithium-ion half-cell are shown in FIG. Fig. 9 , 100 cycles performance see Fig.10 ,Depend on Fig. 9 and 10 It can be seen that the charge / discharge specific capacities of the first, second and third times are 894 / 1026, 864 / 948 and 839 / 905 mAh g −1, and their coulombic efficiencies were 87%, 91%, and 93%, respectively. The coulombic efficiency increased with the number of cycles. At a current density of 0.2C, after 100 cycles, it still maintained 371mAh g −1 The reversible capacity of indicates that the anode material of this embodiment has excellent reversibility and cycle stability.

[0016] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. A method for preparing a SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material, characterized in that: The specific steps are as follows: (1) Ammonia water is added drop by drop into the aqueous solution containing GeO2. After GeO2 is completely dissolved, glucose is added and stirred at room temperature for 1 to 3 hours to obtain solution A. Solution A is added into a high temperature and high pressure reactor and kept at 150 to 200°C for 6 to 24 hours. The solid and liquid are separated and the solid is dried to obtain product B. (2) Dispersing product B uniformly in a deionized water-ethanol mixed solution to obtain a product B dispersion, adding tin tetrachloride to the product B dispersion and mixing uniformly to obtain a solution C, stirring the solution C at room temperature for 2 to 4 hours, washing the precipitate with ethanol by centrifugation, and drying to obtain a product D; (3) Dispersing product D uniformly in an ammonia-ethanol mixed solution to obtain a product D dispersion, adding tetrabutyl titanate to the product D dispersion and mixing uniformly to obtain a solution E, stirring the mixture at room temperature for 1 to 3 hours, washing the precipitate by centrifugation with ethanol, and drying the mixture to obtain a precursor product F; (4) The precursor product F is calcined in an air atmosphere and then cooled to room temperature to obtain a SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material with a hollow core-shell structure.

2. The method for preparing the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material according to claim 1, characterized in that: In step (1), the mass concentration of GeO2 in solution A is 1-5%, the mass concentration of ammonia water is 1-5%, and the mass concentration of glucose is 5-15%.

3. The method for preparing the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material according to claim 1, characterized in that: The volume ratio of ethanol to deionized water in the deionized water-ethanol mixed solution of step (2) is 3:1-5, the mass concentration of product B in solution C is 1-6%, and the mass concentration of tin tetrachloride is 1-6%.

4. The method for preparing the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material according to claim 1, characterized in that: The mass concentration of ammonia in the ammonia-ethanol mixed solution of step (3) is 1-5%, the mass concentration of product D in solution E is 2-7%, and the mass concentration of tetrabutyl titanate is 0.5-3%.

5. The method for preparing the SnO2@TiO2 double-shell encapsulated amorphous GeO2 ternary anode material according to claim 1, characterized in that: The calcination temperature in step (4) is 400-600°C and the calcination time is 2-8 hours.

Citation Information

Patent Citations

  • Lithium-ion battery cathode material GeO2 / C with core-shell structure and preparation method thereof

    CN106025180A

  • Tin dioxide / carbon@ titanium dioxide microsphere composite material for negative electrode of lithium ion battery, preparation method and application thereof

    CN112768648A

  • Preparation method of carbon-coated amorphous micron GeOx spherical particle composite anode material

    CN115224261A

  • Method for preparing nanostructured Ge / GeO2 composite in carbon matrix

    KR1020170129671A